Comparative Analysis of Laparoscopic Nephrectomy Techniques: Inflammatory Biomarker Response and Renal Functional Outcomes - Hasan Güngör (Middle Black Sea Journal of Health Science, 2026)
Objective: To compare perioperative inflammatory markers and renal functional outcomes among different laparoscopic nephrectomy (LN) techniques, and to assess the predictive role of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) for surgical stress.Methods: Thirty-six patients undergoing laparoscopic nephrectomy between February 2024 and January 2026 were retrospectively analyzed. Procedures included laparoscopic partial (LPN), radical (LRN), and simple nephrectomy (LSN). Demographics, operative variables, and inflammatory indices were evaluated. NLR, PLR, and estimated glomerular filtration rate (eGFR) were measured preoperatively and on postoperative day 1. Statistical analysis used ANOVA, Tukey post-hoc, paired t-tests, correlation, and regression.Results: All surgeries were laparoscopic without conversion. Mean warm ischemia time for LPN was 20.1 ± 4.2 min. NLR and PLR rose significantly postoperatively (p < 0.001). LSN showed the largest ΔNLR (6.72 ± 2.80); intergroup difference was not significant (p = 0.356). ΔGFR differed (p = 0.021); LRN had the greatest decline. Regression identified nephrectomy type and baseline GFR as predictors (p < 0.05).Conclusion: Different laparoscopic nephrectomy techniques yield distinct inflammatory and functional profiles. LPN preserves renal function best, while LSN elicits stronger inflammation due to chronic pathology. NLR and PLR are effective, low-cost biomarkers for evaluating perioperative stress.